The Effects of Aerobic Exercise on Oxidative Stress in Older Adults: A Systematic Review and Meta-Analysis - Ye, Yu; Lin, Huiying; Wan, Mingyue; Qiu, Pingting; Xia, Rui; He, Jianquan; Tao, Jing; Chen, Lidian; Zheng, Guohua (Frontiers in Physiology, 2021)
Background: Oxidative stress (OS) plays an important role in the progression of many aging-related diseases. Exercises can delay this kind of progress, but aerobic exercise is the most commonly used type of training among older adults; therefore, its influence needs to be further verified. Methods: A literature search was conducted in eight electronic databases, including Cochrane, EMBASE, PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Wanfang Date, and SinoMed from their inception to April 2020. Methodological quality was assessed using Cochrane RoB tool v2.0 for individual studies, and RevMan 5.3 software was used to perform the meta-analysis. Results: The meta-analysis included 20 studies, involving 1,170 older adults. The results showed that regular aerobic exercise could reduce blood oxidant markers, including malondialdehyde (MDA; SMD=−1.80, 95% CI −2.46 to −1.14, p<0.001) and lipid peroxide (LPO; SMD=−1.12, 95% CI −2.03 to −0.22, p=0.02), and increase the levels of antioxidant factors, such as nitric oxide (NO; SMD=0.89, 95% CI 0.37–1.41, p<0.001), superoxide dismutase (SOD; SMD=0.63, 95% CI 0.25–1.01, p=0.001), and total antioxidant capacity (TAC; SMD=1.22, 95% CI 0.45–1.98, p=0.002), with clear statistical significance. It may also improve the levels of other OS markers, such as 8-OHdG, 8-isoPGF2, VE, and reduced glutathione/oxidized glutathione (GSH/GSSG). Conclusion: Regular aerobic exercise may have a positive effect on the OS levels of older adults by reducing some oxidant markers and increasing antioxidant marker levels.